Synthesis, insecticidal and larvicidal activity of 1-(α or β)- naphthylamidine-1-arylthiocarbamide dihydrochlorides and 4-aryl-3(α or β)-naphthylimino-5-imino-1,2,4-thiadiazolidines - Shankar V.; Pandeya S.N. (My University, 2025)
[No abstract available]